Innervation and Neuronal Control of the Mammalian Sinoatrial Node a Comprehensive Atlas. Issue 9 (30th April 2021) - Hanna, Peter; Dacey, Michael J.; Brennan, Jaclyn; Moss, Alison; Robbins, Shaina; Achanta, Sirisha; Biscola, Natalia P.; Swid, Mohammed A.; Rajendran, Pradeep S.; Mori, Shumpei; Hadaya, Joseph E.; Smith, Elizabeth H.; et al.
Abstract : Rationale: Cardiac function is under exquisite intrinsic cardiac neural control. Neuroablative techniques to modulate control of cardiac function are currently being studied in patients, albeit with variable and sometimes deleterious results. Objective: Recognizing the major gaps in our understanding of cardiac neural control, we sought to evaluate neural regulation of impulse initiation in the sinoatrial node (SAN) as an initial discovery step. Methods and Results: We report an in-depth, multiscale structural and functional characterization of the innervation of the SAN by the right atrial ganglionated plexus (RAGP) in porcine and human hearts. Combining intersectional strategies, including tissue clearing, immunohistochemical, and ultrastructural techniques, we have delineated a comprehensive neuroanatomic atlas of the RAGP-SAN complex. The RAGP shows significant phenotypic diversity of neurons while maintaining predominant cholinergic innervation. Cellular and tissue-level electrophysiological mapping and ablation studies demonstrate interconnected ganglia with synaptic convergence within the RAGP to modulate SAN automaticity, atrioventricular conduction, and left ventricular contractility. Using this approach, we comprehensively demonstrate that intrinsic cardiac neurons influence the pacemaking site in the heart. Conclusions: This report provides an experimental demonstration of a discrete neuronal population controlling a specific geographic region of the heart (SAN) that can serve as a framework for further exploration of other parts of the intrinsic cardiac nervous system (ICNS) in mammalian hearts and for developing targeted therapies. Abstract : Supplemental Digital Content is available in the text.